Revealing genetic markers and evolutionary insights within Piperaceae in chloroplast genome architecture of Indonesian Piper betle - ENDANG RAHMAT; LAURA ANINDITA; NESTI FRONIKA SIANIPAR; KHOIRUNISSA ASSIDQI; YOUNGMIN KANG; KENNETH HAPPY; ADHITYO WICAKSONO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Rahmat E, Anindita L, Sianipar NF, Assidqi K, Kang Y, Happy K, Wicaksono A. 2025. Revealing genetic markers and evolutionary insights within Piperaceae in chloroplast genome architecture of Indonesian Piper betle. Biodiversitas 26: 5906-5919. Piper betle is one of the most significant medicinal plants in Southeast Asian tradition, yet its genomic resources remain limited compared to other members of the genus. In this study, we report the first complete chloroplast genome of an Indonesian isolate of P. betle, providing a much-needed reference for future molecular work. The genome was assembled into 161,313 bp with a typical quadripartite structure consisting of an LSC (88,995 bp), an SSC (18,201 bp), and two nearly identical IRs (27,057 and 27,060 bp). A total of 113 genes were annotated, including 79 protein-coding, 30 tRNA, and 4 rRNA genes. Repeat analysis revealed 70 cpSSRs, markedly fewer than those described in other Piper species, along with 104 long repeats dominated by palindromic types. Sliding-window analysis detected variable regions in ndhG and ndhI in addition to the well-known hotspots ycf1 and rpl32-ndhF, two novel loci that may serve as species-specific markers. Phylogenetic reconstruction clustered the Indonesian isolate with P. hancei, P. nigrum, and P. kadsura, yet comparison with a Chinese isolate indicated paraphyletic placement across two clades which may indicate a role of geographic divergence in shaping plastome evolution. The results of these genomic resources reveal reduced SSR content, novel divergence hotspots in ndhG and ndhI, and the paraphyletic relationship with the Chinese isolate: creating potential in marker development and evolutionary studies, while also laying the groundwork for future applications in conservation and biotechnology.